The Role of Customer Engagement as a Mediator of the Effects of Digital Ad Personalization and Interactive Digital Content on Consumer Trust on TikTok Shop - Muchlis Abbas; Rahmawati Umar; Arnida Arnida (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effect of Digital Ad Personalization and Interactive Digital Content on Consumer Trust, with Customer Engagement as a mediating variable, among TikTok Shop users in the Generation Z segment in Indonesia. Research Method: This study employed a quantitative approach with an explanatory survey design. Data were collected from 200 active TikTok Shop users through purposive sampling using an online questionnaire. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software to test the measurement model, structural model, and mediating effects. Results and Discussion: The results of the study indicate that Digital Ad Personalization and Interactive Digital Content have a positive and significant effect on Customer Engagement and Consumer Trust. In addition, Customer Engagement has a positive effect on Consumer Trust and was found to partially mediate the relationship between Digital Ad Personalization and Interactive Digital Content and Consumer Trust. Implications: These findings suggest that digital marketing strategies that integrate ad personalization and interactive content can increase consumer engagement while strengthening consumer trust in social commerce platforms. Further research is recommended to develop a model by adding other variables and expanding the characteristics of the respondents. Originality: The novelty of this study lies in integrating Digital Ad Personalization, Interactive Digital Content, Customer Engagement, and Consumer Trust into a single PLS-SEM-based mediation model in the context of TikTok Shop in Indonesia.